Kemampuan Fraud Diamond Mendeteksi Kecurangan Pelaporan Keuangan Dimoderasi Ukuran Perusahaan - Sabaruddin Sabaruddin (Jurnal Akuntansi dan Governance, 2022)
This study aims to employ fraud diamond analysis to determine the potential of fraudulent financial statements using quantitative method with secondary data. The banking companies listed on the Indonesia Stock Exchange (IDX) between 2016 and 2020 are chosen with a purposive sampling technique. The results show that financial stability, ineffective monitoring, and a change in director have no significant negative effect on the potential for fraudulent financial statements. Meanwhile, the change of auditor has no significant positive effect on the potential of fraudulent financial statements. Firm size is unable to moderate the effect of financial stability, ineffective monitoring, changes in the auditor, and changes in the Board of Directors on the potential of fraudulent financial statements.